Microbial Processes in Gold Migration and Deposition: Modern Analogues to Ancient Deposits - Mossman, David; Reimer, Thomas; Durstling, Hans (Geoscience Canada, 1999)
Results of selected experimental work on the biomineralization of gold are reviewed against the background of historical accounts. The intrinsic ability of certain plants, and of micro-organisms in particular, to bind metals, functions in diverse ways to dissolve, immobilize, transport, or precipitate gold under a wide range of geological conditions. In exceptional cases, ore deposits may be formed, examples of which may be the phenomenal concentrations of gold in the Witwatersrand paleoplacers of South Africa. These deposits originated on early Earth under atmospheric conditions which may have promoted microbial activity in a continental setting more efficiently and on a larger scale than at present. A complication is that bacterioform gold in mineral deposits may be imitated in every detail by inorganic processes. However, there is now compelling evidence that microorganisms play key roles in influencing the geochemical behaviour of gold, and effecting its precipitation. This is provided by the results of laboratory experiments designed to simulate natural occurrences of gold, and to examine the metal absorption, gold-binding affinities and properties of specific microbes. Résumé Le présent article passe en revue les résultats de certaines expériences dans le domaine de la bio-minéralisation aurifère et considère leur applicabilité aux vues des données historiques de gisements connus. La capacité de certaines plantes et de certains microorganismes en particulier, de mobiliser des ions métalliques peut expliquer la dissolution, l’immobilisation, le transport ou la précipitation de l’or sous une grande diversité de paramètres géologiques. Et, dans certaines conditions particulières, des gisements minéraux peuvent ainsi se constituer; l’extraordinaire concentration d’or du gisement de Witwatersrand en Afrique du Sud pourrait bien en être un exemple. Ces gisements se sont constitués au début de l’histoire de la Terre, dans des conditions atmosphériques qui pourraient avoir favorisé une activité microbienne continentale plus efficace et sur une plus grande échelle que dans les conditions actuelles. Cependant, les formes bactériogéniques aurifères peuvent être imitées dans leurs caractères les plus fins par sa contrepartie inorganique ce qui en complique d’autant l’identification. Il demeure cependant qu’on a maintenant des indications convaincantes de l’importance clé du rôle des microorganismes sur la précipitation et le comportement géochimique de l’or. Ces indications nous viennent de résultats d’expérience en laboratoires visant à simuler les formes naturelles des minéralisations aurifères et à étudier les phénomènes de l’absorption des métaux, les affinités de l’or et les caractéristiques de microbes particuliers.